2002
DOI: 10.1590/s0034-72992002000300004
|View full text |Cite
|
Sign up to set email alerts
|

Achados clínicos e endoscópicos em crianças com estridor

Abstract: Palavras-chave: estridor, fibronasolaringobroncoscopia, anomalias congênitas da laringe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 14 publications
0
7
0
1
Order By: Relevance
“…Even though laryngomalacia is the main cause of congenital stridor in childhood 9 , many Otorhinolaryngologists have questioned the clinical and/or surgical treatment of these patients as well as their diagnoses. There are no consensus or very clear parameters in the literature about the exams required for the diagnosis (flexible videonasofibroscopy and/or rigid bronchoscopy) and clinical and/or surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Even though laryngomalacia is the main cause of congenital stridor in childhood 9 , many Otorhinolaryngologists have questioned the clinical and/or surgical treatment of these patients as well as their diagnoses. There are no consensus or very clear parameters in the literature about the exams required for the diagnosis (flexible videonasofibroscopy and/or rigid bronchoscopy) and clinical and/or surgical treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Laryngomalacia is the most common cause of congenital stridor. In a previous study, Lubianca et al 26 showed that laryngomalacia accounted for 40.8% of the cases of stridor assessed through fiberoptic nasolaryngoscopy and for up to 58% of the cases of stridor in subjects under 30 months. In this study, stridor was the most frequently found symptom leading to the diagnosis of laryngomalacia with all patients being examined through nasopharyngolaryngoscopy.…”
Section: Discussionmentioning
confidence: 94%
“…Laryngeal malformations are more prevalent in males and manifest within the first months of life 2 , 3 , 6 . The laryngeal involvement seen in the case presented extended from the anterior to the posterior direction, had a round central-posterior lumen, and was accompanied by signs consistent with an uncommon and potentially severe case of laryngeal membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital anomalies rank among the top causes of stridor in neonates and infants. Laryngomalacia stands out as a frequent causing agent, along with less prevalent occurrences of laryngeal membrane, laryngeal atresia and subglottic stenosis 1 , 2 , 3 . Laryngeal membranes are thin translucent formations consequent to failed laryngeal lumen recanalization during embryogenesis 1 , 4 .…”
Section: Introductionmentioning
confidence: 99%